FEATURES OF FORMATION, DYNAMICS, DISCHARGE AND WATER INTAKE OF GROUNDWATER ON HIGH MARKINGS: (case of study the Lake Sevan catchment basin) (Proceedings of the YSU C: Geological and Geographical Sciences, 2019)
To solve the problems of catchment of groundwater at high elevations, it is practically important to know the course of the perennial change in various average monthly discharge of the springs. In general, changes in the discharge of springs of the investigated territory (especially volcanic areas) are subject to the law of vertical zonality. The proposed task allows to identify perspective areas for targeted field research. Among the field research method we recommend geophysical ones, which have been successfully used in the search for groundwater at high elevations in a number of volcanic areas.
Keywords: groundwater; springs; Lake Sevan; precipitation; filtration; geophysical methods; pool; waterproof layer; catchment facilities recommended scheme